2008
DOI: 10.1002/prot.21547
|View full text |Cite
|
Sign up to set email alerts
|

Lattice simulations of cotranslational folding of single domain proteins

Abstract: We use lattice protein models and Monte Carlo simulations to study cotranslational folding of small single domain proteins. We show that the assembly of native structure begins during late extrusion stages, but final formation of native state occurs during de novo folding, when all residues are extruded. There are three main results in our study. First, for the sequences displaying two-state refolding mechanism de novo cotranslational folding pathway differs from that sampled in in vitro refolding. The change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 45 publications
3
12
0
Order By: Relevance
“…The use of lattice models and MC simulations has a long tradition in the study of protein folding [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], and, more recently, in exploring the related problems of co-translational folding [36], protein aggregation [37] and binding [38], just to mention a few examples. A main advantage of these minimalistic models over alternative off-lattice representations is their computational efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The use of lattice models and MC simulations has a long tradition in the study of protein folding [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], and, more recently, in exploring the related problems of co-translational folding [36], protein aggregation [37] and binding [38], just to mention a few examples. A main advantage of these minimalistic models over alternative off-lattice representations is their computational efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Computational models have provided evidence that nascent chains may adopt partial structures similar to the corresponding parts of the complete protein [52]. Other lattice studies present a differing view of cotranslation where nascent peptides can remain largely unstructured until the final stages of synthesis (estimated to be when 90% or more of the protein has been extruded) [53]. This finding is dependent on the involvement of the C-terminal in tertiary interactions, and may not be applicable to all proteins.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is dependent on the involvement of the C-terminal in tertiary interactions, and may not be applicable to all proteins. There is also evidence arising from lattice models that cotranslational folding pathways and refolding pathways are different [53]. Computational simulations of real proteins folding cotranslationally compared to refolding from a denatured state show mixed results.…”
Section: Introductionmentioning
confidence: 99%
“…In the Monte Carlo simulations of three elongating nascent chains modeled on a lattice, Wang & Klimov (84) showed that long-range tertiary interactions, responsible for stabilizing these proteins' native states, affect cotranslational folding kinetics by slowing it down. The marginal stability of these sequences and the stabilizing, long-range interactions allow folding to occur only after more than ∼90% of the protein is synthesized, when the amino acids toward the C terminus become available to form native contacts.…”
Section: Figurementioning
confidence: 99%